U-47700: A Not So New Opioid. Issue 1 (11th October 2017) - Rohrig, Timothy P; Miller, Samuel A; Baird, Tyson R
Abstract: U-47700 was developed by the Upjohn Co. in the 1970s as part of their search for a selective μ-opioid agonist with similar potency as morphine. U-47700 has re-emerged recently in the illicit drug market and is easily and cheaply obtained via the internet as well as on the street, many times falsely sold as another drug. Several fatalities from U-47700 have been reported in scientific literature, often in combination with other intoxicants. This case report describes the first death in south-central Kansas resulting solely from U-47700 intoxication: a 26-year-old white male found dead in his bedroom with apparent drug paraphernalia. Autopsy findings were consistent with opioid overdose, but toxicological examination, utilizing immunoassay and instrumental techniques, was negative for opioids. U-47700 was detected in a comprehensive alkaloid screen by GC/MS and GC-NPD, and quantitation was performed using GC-NPD on a variety of specimens to provide a full tissue distribution. Quantitation of U-47700 in this individual revealed the following: heart blood 0.26 mg/L, femoral blood 0.40 mg/L, vitreous fluid 0.09 mg/L, brain 0.38 mg/kg, liver 0.28 mg/kg and urine 4.6 mg/L.